Semiconducting Nanoparticles: Single Entity Electrochemistry and Photoelectrochemistry - Mathuri, S.; Zhu, Yuanhang; Margoni, Mudaliar Mahesh; Li, Xiuting (Frontiers in Chemistry, 2021)
Semiconducting nanoparticles (SC NPs) play vital roles in several emerging technological applications including optoelectronic devices, sensors and catalysts. Recent research focusing on the single entity electrochemistry and photoelectrochemistry of SC NPs is a fascinating field which has attained an increasing interest in recent years. The nano-impact method provides a new avenue of studying electron transfer processes at single particle level and enables the discoveries of intrinsic (photo)electrochemical activities of the SC NPs. Herein, we review the recent research work on the electrochemistry and photoelectrochemistry of single SC NPs via the nano-impact technique. The redox reactions and electrocatalysis of single metal oxide semiconductor (MOS) NPs and chalcogenide quantum dots (QDs) are first discussed. The photoelectrochemistry of single SC NPs such as TiO2 and ZnO NPs is then summarized. The key findings and challenges under each topic are highlighted and our perspectives on future research directions are provided.